Analysis of Factors Associated with Temporal Hollowing after Pterional Craniotomy - Thanakorn Thiensri; Akaluk limpoka; Chairat Burusapat (Indian Journal of Plastic Surgery)
Background Temporal hollowing is a common complication after pterional craniotomy. Etiologies of hollowing are still in debate and inconclusive. The objective of this study is to determine the etiology and predictive factors of temporal hollowing after pterional craniotomy. Methods A retrospective study of patients who underwent pterional craniotomy was conducted. Inclusion criteria included older than 18 years, having undergone unilateral pterional craniotomy, and with no craniofacial anomaly or temporal defect. Volumes of bone, temporalis muscle, and extratemporalis layer were calculated. Results A total of 51 patients were included. Bone volumes of surgical and nonsurgical sites were 219.12 + 23.02 cm﻿﻿3, and 228.39 + 22.76 cm﻿﻿3, respectively (p = 0.04). Difference of bony volume was 9.10 cm﻿﻿3 (3.99%). Volumes of temporalis muscle in surgical and nonsurgical sites were 12.86 + 3.95 cm﻿﻿3, and 18.10 + 6.08 cm﻿﻿3, respectively (p < 0.005). Difference of muscle volume was 5.08 cm﻿﻿3 (28.32%). Volume of extratemporalis soft tissue in surgical and nonsurgical sites were 11.99 + 5.70 cm﻿﻿3, and 17.31 + 7.76 cm3, respectively (p < 0.005). Difference of soft tissue volume was 5.56 cm﻿﻿3 (31.68%). No statistical significance of the difference of bony, muscle, and soft tissue volumes were found between causes of disease, operative time, and postoperative radiation. Conclusions Hollowing after pterional craniotomy is an unavoidable result. Bone, temporalis muscle, and soft tissues are combined etiologies. No predictive factors including age, sex, causes, operative time, radiation, and surgical technique are demonstrated. Volume of temporal area reduction was 19.74 cm﻿﻿3. Immediate reconstruction is recommended and volume of reconstruction is calculated from preoperative imaging.